Perbandingan Metode Double Exponential Smoothing dan Least Square untuk Sistem Prediksi Hasil Produksi Teh - Muhammad Bagus Nurkahfi; Victor Wahanggara; Bakhtiyar Hadi Prakoso (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2020)
Tea is one of the mainstay commodities of Indonesian plantation. In order to meet market demand, it is necessary to plan the right production needs, so that the amount of production capacity and market demand is balanced. To meet the needs of the right production requires good planning. The way that can be done is by making predictions. In this study, the prediction of tea production was carried out using the Double Exponential Smothing and Least Square methods. From the test results, it was found that the MAPE value of the Double Exponential Smoothing method, the most optimal α value is α 0.1 with a MAPE value of 18.084% and for the Least Square method the MAPE value is 17.008%.